How To Challenge The Life Women Resiliency In Acehnese Matrilocal System: Philological and Anthropological Approaches - Fakhriati, Fakhriati; Kustini, Kustini; Mu’jizah, Mu’jizah; Fuad, Muhammad; Warnis, Warnis (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2023)
The matrilocal system has had a positive effect on women in Aceh. This system has enabled them to become more resilient in facing life's challenges for themselves, their families and their communities. This study is a qualitative study with philological and anthropological approaches used to study Acehnese manuscripts that are relevant to the theme of matrilocality. In-depth interviews, manuscript studies and observations were also conducted to understand matrilocality practices in Aceh, particularly in the Pidie regions. In this way, historical and empirical knowledge of Aceh's matrilocal system is obtained. It was found that the matrilocal system had raised the status and enthusiasm and resilience of Acehnese women in wading through life as individuals, family members, and part of Acehnese society. Philologically, historically and anthropologically a harmonious life is seen in the matrilocal system, Acehnese women make it possible to face life's challenges, such as raising children for a successful life; maintain good communication with parents, neighbors and the community; and managing household finances. This diversity of matrilocal traditions can contribute to the status and resilience of women in the Indonesian nation-state.